Patient Diversity in Breast Imaging: Barriers and Potential Solutions. Issue 1 (29th October 2020) - Patel, Miral M; Parikh, Jay R
Abstract: Recent reports have highlighted disparities in breast cancer care related to patient diversity. Breast radiologists represent the face of breast imaging and are key players in advocating for patients to reduce these disparities. Diversity-related barriers for breast imaging patients, as they journey from screening to survivorship, include impediments to access and quality of care, gaps in communication, and lack of knowledge in both providers and patients. Potential strategies for overcoming these specific barriers include "culturally tailored" nurse navigators, mobile mammography, improved communication, patient and provider education, and breast radiologist involvement in advocacy efforts promoting diversity. As current trends in recommendations and guidelines for breast imaging include more numerous and advanced imaging modalities, it is important to acknowledge and address diversity-related disparities.